Application of Sharia Principles in Planning and Designing Pondok Pesantren in Indonesia: Case Study: Pondok Pesantren Al Fath Ma’had in Palembang, South Sumatera - Doni Fireza (Journal of Architecture, Planning and Construction Management, 2020)
Pondok Pesantren (Islamic Boarding School) as one of the educational institutions in Indonesia, which emphasizes on Islamic religious education, have had different and specific approach in the planning and designing of its facilities, compared with the process of planning and designing the school in general. Although there is no specific design typology of the pondok pesantrenâ€™s buildings and facilities, the planning, designing and development process of its contains a special approaches using the Sharia principles derived from the Islamic jurisprudence known as Fiqh. The acculturation of pesantren educational organizations and formal educational organizations such as public school, along with the architect’s involvement in the pondok pesantrenâ€™s development process in modern times can potentially obscure the Islamic values in the life of pondok pesantren, where the principles and values of sharia should be the main characteristics of pondok pesantren itself. This paper studied the principles of Sharia and its application in the process of planning, designing and construction of a sharâ€™i pondok pesantren in Indonesia, through a case study of Pondok Pesantren Al Fath Maâ€™had in Palembang. Islamic Sharia principles in the development of pondok pesantren are gained through the study of literature and the books of Fiqh as well as interviews with experts of Islamic law. Application of Sharia principles in the planning and designing of the pondok pesantren covers ranging from the determination of the legal status of the site; mosque planning, laws and conditions attached to the mosque; zoning activities as well as planning and designing of buildings and supporting facilities; dormitory planning; rules of interior design related to pesantrenâ€™s style teaching-learning activities; until the affairs of Waqf of the residential buildings of Kyai (school headmaster) or teachers.